Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Kualitas Kerja Di PT XYZ Dalam Program Listrik Prabayar Di Jakarta Pusat - Eva Krisna Wati Limbong; Nurvi Oktaviani (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This research aims to analyze the influence of work discipline and job satisfaction on the work quality of PT employees. PT XYZ in the prepaid electricity program in Central Jakarta. The research sample was 40 respondents using the Slovin formula. Based on the results of this research, work discipline (X1) has a positive and significant effect on work quality (Y), with a significance of 0.006 <0.05. Job satisfaction has a positive and significant effect on work quality (Y) with a significance level of 0.036 <0.05. Simultaneously work discipline (X1) and job satisfaction (X2) have a positive and significant effect on the work quality of PT employees. PT XYZ in the prepaid electricity program in Central Jakarta (Y) from F count > F table (19.723 > 2.38) with a significance level of 0.000 < 0.05. The coefficient of determination results obtained R Square 0.516 or 51.6%. influenced by work discipline (X1) and job satisfaction (X2) while the remainder was influenced by the contribution of other variables which were not operationalized by researchers, amounting to 48.4 percent.